(untitled) (World Bulletin of Public Health, 2023)
The class of suckers includes about 3,000 species of parasitic flatworms. In terms of their structure, suckers are close to ciliates, but as a result of living with parasites, their body structure is simplified. The body of suckers is leaf-like, and there are two suckers characteristic of this class: oral sucker and abdominal sucker. With the help of both suckers, suckers cling to the body of their master. In addition, the mouth sucker also serves to suck food. Their body is covered with a skin-muscle bag.